Combining graphical scenarios with a requirements management system - Jiang, Bo (University of Ottawa (Canada), 2005)
Scenarios have gained in popularity for the description of functional requirements. However, scenarios cannot specify all types of requirements, and often they are expressed separately from other requirements. In order for scenarios to be used in cooperation with complementary general requirements, both views must be linked in a way that supports traceability, navigation, and analysis. This thesis proposes an approach to introduce graphical scenarios (represented as Use Case Maps---UCMs) into a requirements management system (namely, Telelogic DOORS) and to maintain relationships from and to external requirements as both views evolve over time. In the first part of the thesis, an export mechanism is added to the Use Case Map Navigator tool that enables the export of UCM models in a format that can be understood by the target requirements management system, i.e., DOORS. In the second part of the thesis, DOORS is enhanced with an import mechanism to create or update UCM models based on the information generated by the UCM tool. Finally, the approach is illustrated with a case study (a supply chain management business process) that demonstrates how the UCM model, the external requirements, and their links can be kept consistent as both views evolve.
Keywords: Computer Science.